Il supercoelium di San Marco a Roma tra disegno e costruzione - Bova, Sara (Opus Incertum, 2018)
Constructed between May 1467 and February 1468 by the carpenters Giovannino and Marco di Pietro de’ Dolci and the illuminator Giuliano degli Amadei, the wooden coffered ceiling at San Marco al Campidoglio constitutes one of the early works carried out under Pope Paul II's for the renewal of the basilica, to which he had been appointed as a cardinal, as part of the wider fabbrica of the complex of palazzo Venezia. This artwork represents the first case of the use of this all’antica solution for the ceiling of a church hall, following the tradition begun by Brunelleschi at San Lorenzo in Florence. However, regarding the details of the mouldings and the remarkable variety of shapes used for the flowers placed at the centre of each coffer, the ceiling of San Marco shows a closer continuity with  examples in stone from the Roman Imperial period, such as the ones decorating the intradoses of the arch of Titus and of the ptéron of the temple of Mars Ultor.